Tumores del encéfalo - Rocca, Esteban (1956)
On the occasion of the Second Neuropsychiatric Day, organized by the Society of Neuropsychiatry, Forensic Medicine and Allied Sciences, was considered urgent need to develop the theme of brain tumors on the basis of measurable progress due to the efforts of scientists, practitioners of the neuroscience, electrophysiology, neurohistopatholgy, forcing us to do a review, especially in our country, still young, but with two decades of a systematic development of this specialty, currently set allowing an approximate balance. Neurosurgery of Peru has to his credit the solid neuropsychiatric struture that, many times, has enabled our best exponents switch on par in international scientific meetings. These and many other reasons forced us to measure the extent of our responsibility to accept the development of such a vast and interesting subject.